Solid pseudopapillary neoplasm of pancreas: a rare presentation - Memon, Mohd Jafar; Kujur, Pratima; Siddique, Rabia Parveen; Gupta, Yashita (International Journal of Research in Medical Sciences, 2017)
Pancreatic neoplasms are rare in children and have a different histo-logic spectrum and prognosis than those in adults. Pancreatoblastoma is the most common pancreatic neoplasm in young children. Solid pseudopapillary neoplasm occurs in adolescent girls. It is heterogeneous in internal architecture, with a mixture of solid and cystic hemorrhagic and necrotic elements. All pancreatic neoplasms in children are capable of producing metastases, usually to the liver and lymph nodes; however, on the whole, these tumors have a better clinical outcome than most pancreatic tumors in adults. We present a case of solid pseudopapillary neoplasm with a liver metastasis in a 13 year old male patient.